Proteomic analysis of whey from bovine colostrum and mature milk - Luciana Pacheco Golinelli; Carlos Adam Conte-Junior; Vânia Margaret Flosi Paschoalin; Joab Trajano Silva (Brazilian Archives of Biology and Technology, 2011)
The aim of this study was to standardize a methodology to obtain two-dimensional (2D) maps of whey proteins from bovine colostrum and mature milk, using two-dimensional electrophoresis, in order to identify the minor proteins by matrix-assisted laser desorption/ionization tandem time-of-flight mass spectrometry (MALDI TOF/TOF MS). A total of 38 proteins were identified, 20 spots in the colostrum whey and 18 in the mature milk whey; 5 of them were identified for the first time.